2014
DOI: 10.1016/j.dnarep.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sgs1 and Exo1 suppress targeted chromosome duplication during ends-in and ends-out gene targeting

Abstract: Gene targeting is extremely efficient in the yeast Saccharomyces cerevisiae. It is performed by transformation with a linear, non-replicative DNA fragment carrying a selectable marker and containing ends homologous to the particular locus in a genome. However, even in S. cerevisiae, transformation can result in unwanted (aberrant) integration events, the frequency and spectra of which are quite different for ends-out and ends-in transformation assays. It has been observed that gene replacement (ends-out gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 88 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…We observed an Exo1‐dependent loss of genes, as well as gene duplication events, in cells lacking telomeres. Exo1 has been previously documented to facilitate or inhibit chromosomal duplication following other type of insults, through a checkpoint‐dependent (Kaochar et al ., 2010) or homology‐directed repair (HDR) dependent mechanism (Štafa et al ., 2014). However, the palindrome formation in PAL cells is both HDR‐independent (PALs are rad52∆ ) and checkpoint‐independent (in rad9∆ and rad24∆ strains) and therefore occurs by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed an Exo1‐dependent loss of genes, as well as gene duplication events, in cells lacking telomeres. Exo1 has been previously documented to facilitate or inhibit chromosomal duplication following other type of insults, through a checkpoint‐dependent (Kaochar et al ., 2010) or homology‐directed repair (HDR) dependent mechanism (Štafa et al ., 2014). However, the palindrome formation in PAL cells is both HDR‐independent (PALs are rad52∆ ) and checkpoint‐independent (in rad9∆ and rad24∆ strains) and therefore occurs by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, replicative senescence is induced by p53 and other checkpoint proteins inactivated in cancers (Shay et al ., 1991; Sugrue et al ., 1997; Schmitt et al ., 2002). Moreover, cancers may originate from cells with telomere attrition (Meeker et al ., 2004) or sometimes with acute telomere losses, due to chromosome fragmentation (Štafa et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Telomeres shorten prematurely in certain diseases and genetic syndromes, for example, liver cirrhosis, pulmonary fibrosis, and dyskeratosis congenita ( Alder et al 2011 ; Batista et al 2011 ; El-Chemaly et al 2011 ). Moreover, telomeres can be lost completely, as in progenies of human lymphocytes exposed to heavy ions, or during chromothripsis ( Durante et al 2006 ; Štafa et al 2014 ).…”
mentioning
confidence: 99%
“…Lithium acetate transformation was done as described previously ( 28 ) but since it was observed that the efficiency of transformation in natural isolates was lower than in commonly used laboratory strains, cells were first allowed to recover for 30 min in rich YPD medium and then plated on selective SC-Ura plates. Isolation of the genomic DNA was performed as described previously ( 29 ) and molecular analysis of transformants was done by Southern blotting ( 30 ) using dioxigenin (DIG)-labelled ADE2 gene (Roche, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%